Research of forming and sintering processes of copper powder blanks for equal channel angular pressing - S. A. Kotov; R. A. Parshikov; S. V. Ganin (Литьë и металлургия)
Copper-based powder materials have found their application in many industries. These include classical powder metallurgy, automotive and aviation industries, microelectronics, instrument engineering, and nanotechnology. In this paper, the processes of forming and sintering copper powders obtained by various methods are considered. The main part of the research was carried out on powders of the PMS-1 brand obtained by electrolysis. Four batches of samples (18 pieces each) were pressed at different pressures. Based on the results of the research, a molding mode was proposed, which should ensure the density of blanks not less than 70 % of the density of compact material. To find the simplest and most rational modes of sintering blanks, the process was carried out in air and in dissociated ammonia. The parameters of the samples were calculated after each technological operation, and the volume shrinkage of the samples was calculated depending on the initial density. Draft tests were carried out. Sediment tests were performed up to a maximum pressure of 400 MPa. Despite the fact that the degree of high-altitude deformation was 37–40 %, none of the samples collapsed during the tests, and no visible cracks were observed. Based on preliminary experiments, the masses and forming modes of rectangular blanks that were used for equal channel angular pressing were calculated. Equal channel angular pressing was performed for two samples parties obtained using different sintering modes. When pressing the first samples party, the lack of the required level of back pressure led to either a complete or significant violation of the material integrity. Before pressing the samples of the second party, a copper sample was previously placed into the channel to create a natural backpressure. It was also possible in principle to carry out the process of equal channel angular pressing of porous sintered workpieces without violating the integrity of the material.